مشكلات تنفيذ الأنشطة التربوية الإسلامية وحلّها في المدرسة الثانوية المحمدية الثالثة جيتيس فونوروكو جاوى الشرقية - Nurul Salis Alamin; Khairul Umam (At-Ta'dib, 2017)
Islamic Education is one of important subject to improve the good character of student, but the implementation in schools is not in accordance with what is expected. One example, after learning 12 years in school, there are students who have not been able to read the Qur'an properly and correctly. Therefore, researchers want to examine the problematic implementation of religious activities in junior high school, namely SMP Muhamdiyah 3 Jetis Ponorogo East Java. This research is a qualitative research, used three method of data collection that is: 1. interview, 2. observation, 3. Documentation. For data analysis researcher use method Miles and Huberman covering three step that is: data collecting, data reduction, and conclusions. The results of this study show: 1. Islamic Education activities conducted by the school are weekly activities such as Read Al-Quran, Tahfidz Quran and public speaking; daily activities, namely Tadarus Al-Qur'an, Sholat Dhuha and Sholat Dzuhur congregation, 2. Problematic in the implementation of activities in schools are: Problems in terms of teachers are the lack of teachers, cooperation between them and lack of good example; The problem in terms of time are the lack of time available and less precise in the timing; Problems in terms of students are the number of students who do not read Al-Qur'an, joke when activities and many do not follow the activity. 3. The solution of the problems are: for the teacher's solution are to increase the number of teachers, build cooperation among teachers and set a good example for the students; the solution in terms of time are a good time management and the addition of time appropriate to the state of the student; the solutions in terms of students are to advise students on the importance of all Islamic religious education activities and to give warning to the jokes when the activities are held.